Knocking down expression of the auxin-amidohydrolase IAR3 alters defense responses in Solanaceae family plants - D'ippólito, Sebastián (2016)
In plants, indole-3-acetic acid (IAA) amido hydrolases (AHs) participate in auxin homeostasis by releasing free IAA from IAA-amino acid conjugates. We investigated the role of IAR3, a member of the IAA amido hydrolase family, in the response of Solanaceous plants challenged by biotrophic and hemi-biotrophic pathogens. By means of genome inspection and phylogenic analysis we firstly identified IAA-AH sequences and putative IAR3 orthologs in Nicotiana benthamiana, tomato and potato. We evaluated the involvement of IAR3 genes in defense responses by using virus-induced gene silencing. We observed that N. benthamiana and tomato plants with knocked-down expression of IAR3 genes contained lower levels of free IAA and presented altered responses to pathogen attack, including enhanced basal defenses and higher tolerance to infection in susceptible plants. We showed that IAR3 genes are consistently up-regulated in N. benthamiana and tomato upon inoculation with Phytophthora infestans and Cladosporium fulvum respectively. However, IAR3 expression decreased significantly when hypersensitive response was triggered in transgenic tomato plants coexpressing the Cf-4 resistance gene and the avirulence factor Avr4. Altogether, our results indicate that changes in IAR3 expression lead to alteration in auxin homeostasis that ultimately affects plant defense responses.